ANALISIS PENGARUH INTELLECTUAL CAPITAL DAN CORPORATE GOVERNANCE TERHADAP FINANCIAL PERFORMANCE - Ningrum, Nora Riyanti; Rahardjo, Shiddiq Nur (Diponegoro Journal of Accounting, 2012)
The purpose of this study is to investigate the relationship between intellectual capital and financial performance and the relationship between corporate governance and financial performance. This study is replicated from Ulum (2008). Meanwhile Ulum (2008) modified Firer and Williams (2003). Ulum (2008), Firer and Williams (2003) found that overall intellectual capital significantly affected to financial performance. The difference between this study and Ulum’s (2008) is that this study does not merely investigate the relationship between intellectual capital and financial performance but also the relationship between corporate governance and financial performance. Corporate governance needs unveiling as stated in the signalling theory that the firm should give much more information about the firm to stakeholder. By using Pulic Value Added Intellectual Coefficient (VAICTM) model to measure intellectual capital. The efficiency of value added (VAICTM) has three major components of firms resources (physical capital, human capital, and structural capital). Corporate governance was measured by using three proxies (management ownership, institutional ownership, and proportion of independent board) and financial performance was measured by using one proxy (ROA). Data were drawn from 54 listed financial firms in Indonesia Stock Exchange for three years (2009-2011). The analysis method used multiple regression. Classic assumption test showed that data were normal, so that the regresion could be implemented properly. The results showed that intellectual capital positively affected future financial performance (ROA). In contrast, management ownership did not affect future financial performance (ROA), in the same way institutional ownership did not affect future financial performance (ROA), however proportion of independent board negatively affected future financial performance (ROA). It can be concluded thus intellectual capital can be used to enhance financial performance if the firm enable to measure it accurately. Meanwhile corporate governance still can not be proven to be used to enhance financial performance.